Symposium on Timber and Allied Products - a Report - Mathur, G. C. (Indian Forester, 1959)
The National Buildings Organization, Ministry of Works, Housing and Supply, Government of India organized a symposium on "Timber and Allied Products" at New Delhi, from 18th to 22nd May, 1959. The Symposium was attended by delegates, numbering over 100, connected with timber resources, industry, utilization and research. Some foreign experts also participated in the deliberations. The discussion of 54 technical papers, which were presented at the symposium in five technical sessions broughtforth important conclusions and recommendations. Based on the deliberations a resume of the symposium is presented in this article.